CaSnO 3 obtained by modified Pechini method applied in the photocatalytic degradation of an azo dye - Lucena, G. L.; Lima, L. C. De; Honório, L. M. C.; Oliveira, A. L. M. De; Tranquilim, R. L.; Longo, E.; Souza, A. G. De; Maia, A. Da S.; Santos, I. M. G. Dos (Associação Brasileira de Cerâmica, 2017)
Abstract Pure forms of alkaline-earth stannates with perovskite structure (ASnO3, A= Ca2+, Sr2+, Ba2+) have been used as photocatalysts. In this work, CaSnO3 perovskite sample was synthesized by a modified Pechini method at 800 ºC and characterized by X-ray diffraction (XRD), UV-visible spectroscopy, infrared spectroscopy and Raman spectroscopy. The photocatalytic degradation of remazol golden yellow (RNL) dye under UV radiation was evaluated. The XRD pattern showed that the synthesis method favored the orthorhombic CaSnO3 crystallization. According to the Raman spectrum, a material with high short-range order was obtained despite of the relatively low synthesis temperature, compared to the solid-state reaction one. The highest photocatalytic activity was attained at pH 3, which presented 51% discoloration and improved activity of 35% compared to discoloration solely due to adsorption (absence of radiation). The point of zero charge (PZC) and the photocatalytic results indicated that a direct mechanism prevailed at pH 3, whereas an indirect mechanism prevailed at pH 6.

Resumo Estanatos de metais alcalinos terrosos na forma pura com estrutura perovskita (MSnO3, M= Ca2+, Sr2+, Ba2+) têm sido utilizados como fotocalisadores. Neste trabalho, perovskita de CaSnO3 foi sintetizada pelo método Pechini modificado, em 800 ºC, e caracterizada por difração de raios X, espectroscopia de UV-vis, espectroscopia de infravermelho e espectroscopia Raman. Avaliou-se a degradação fotocatalítica do corante remazol amarelo ouro (RNL) sob luz ultravioleta. O difratograma de raios X mostrou que o método de síntese utilizado favoreceu a formação do CaSnO3 ortorrômbico. O espectro Raman indicou que um material com elevada ordem a curto alcance foi obtido apesar da temperatura de síntese relativamente baixa, em comparação ao método do estado sólido. A maior atividade fotocatalítica foi alcançada em pH 3, que apresentou descoloração de 51% e aumento de atividade de 35% em relação à adsorção (ausência de radiação). O ponto de carga zero (PZC) e os resultados fotocatalíticos indicaram que em pH 3 existiu uma predominância de um mecanismo direto, enquanto em pH 6 prevaleceu o mecanismo indireto.
CaSnO 3 obtido pelo método Pechini modificado aplicado na degradação fotocatalítica de um azo corante
Keywords: CaSnO3; photocatalysis; dye degradation; CaSnO3; fotocatálise; degradação de corantes